Identification of the degradation of bread starch by saliva (salivary amylase enzyme) using Lugol 2%: an experimental proposal (Research, Society and Development, 2022)
Animal Physiology is the area of Biology that is concerned with studying the functioning of the organism, however, it has many terms and processes, being a challenge for the full learning of students. Thus, nowadays, making the contextualization of this knowledge easier and more exciting is a constant challenge for the teacher. Added to this, classes based on the purely expository model can cause disinterest and attention deficit in students. To overcome such obstacles, the present work has as main objective, an experimental proposal, the students of the 2nd grade of High School, in the discipline of Biology, facilitating the contextualization of the Physiology of the human Digestive System, regarding the action of the salivary amylase enzyme (ptyalin) in bread starch, using Lugol 2%. As a result, students will realize that Lugol 2% will color the bread starch, with a very dark color, to the detriment of the complexation of the Iodine molecules of the said reagent, with the branched structure of the bread (polysaccharide). However, with the treatment that contains the piece of bread, Lugol 2% and saliva, the complexation of the Iodine molecules of the Lugol 2% reagent will not occur and its dark color will soon disappear, due to the fact that the administered saliva contains the enzyme Salivary amylase (ptyalin), which will break down the starch in bread (polysaccharide), turning it into disaccharide (maltose). Thus, it is expected that the involvement of students and discussions mediated by the teacher of the discipline, can facilitate the learning of the proposed theme, in addition to instigating students in the act of scientific experimentation. Finally, we can point out that the proposed experimental activity can be adapted to be carried out in the classroom, or at home by the students themselves, not requiring a physical laboratory structure, with glassware or expensive equipment.